FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU PENCEGAHAN COVID-19 PADA LANSIA YANG DILAKUKAN ANGGOTA KELUARGA USIA PRODUKTIF DI MALAKA SARI - Ramadhina Karimah (2022)
The family that supposed to be the safest place during the pandemic could happening unexpected transmission of COVID-19. The variety of ages causes different risk of transmission and immunity of each family member. The productive age has a high risk of transmission with low mortality still can transmit virus to family members, especially to elderly in the home. Family's role is very important to protect the elderly. This study aims to determine what factors influence the behavior of COVID-19 prevention carried out by productive-aged family members in the elderly who lives at RT 06/09 Malaka Sari. This is a descriptive study with a cross-sectional method and total sampling from 43 people who lives with elderly. The data results were analyzed using univariate, bivariate, and multivariate analysis with logistic regression model. Age group, gender, and knowledge were not related to COVID-19 prevention behavior (p-value > 0.05). Factors that have a significant relationship with COVID-19 prevention behavior are family support (p-value=0.000) and attitude (p-value=0.000). The most dominant predictor factor is attitude. People with positive attitudes are more likely to carry out good prevention behaviors (OR=17,477). The family support variable also had an influence, but it was fewer than the attitude variable (OR=9.507). People are expected to continue to do prevention both for themselves and for their families. Prevention of COVID-19 can be improved with the help of public health centers, regional leaders, and government to continue raising public awareness to protect their families